2021
DOI: 10.2486/indhealth.2020-0236
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on the application of electrospun nanofiber webs for the air sampling of crystalline silica

Abstract: The aim of the present study was to first fabricate an electrospun PVC nanofiber web and then assess its applicability in sampling and measuring the concentration of airborne crystalline silica by comparing analysis results with a commercial PVC membrane filter under different ranges of airborne silica concentration. A filtration performance comparison was also made between an electrospun PVC web with nano-sized fibers and a commercial PVC membrane filter. Overall, the measured concentration of silica by the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…For example, Gao et al [ 149 ] used polyvinyl chloride (PVC) to prepare nanofiber filters and successfully realized the removal of particle pollution under conditions of high humidity, which mainly took advantage of the hydrophobicity of PVC. The PVC filtration membrane prepared by Farhangian et al [ 150 ] using the electrospinning process was 1.022 times more effective than common commercial PVC filters, with a higher filtration efficiency and a lower pressure drop, which was mainly attributed to the nanoscale materials prepared by the electrospinning process. The pure polymer air-filter membranes are summarized below, in Table 2 .…”
Section: Electrospun Fibrous Membranes For Particle Filtrationmentioning
confidence: 99%
“…For example, Gao et al [ 149 ] used polyvinyl chloride (PVC) to prepare nanofiber filters and successfully realized the removal of particle pollution under conditions of high humidity, which mainly took advantage of the hydrophobicity of PVC. The PVC filtration membrane prepared by Farhangian et al [ 150 ] using the electrospinning process was 1.022 times more effective than common commercial PVC filters, with a higher filtration efficiency and a lower pressure drop, which was mainly attributed to the nanoscale materials prepared by the electrospinning process. The pure polymer air-filter membranes are summarized below, in Table 2 .…”
Section: Electrospun Fibrous Membranes For Particle Filtrationmentioning
confidence: 99%
“…Recently, Farhangian et al [56] demonstrated that electrospun nanofibres manufactured from PVC have superior filtration performance compared to commercial PVC filters, in terms of higher filtration efficiency and lower pressure drop. They tested electrospun PVC membranes by sampling airborne crystalline silica, which is classified as a class 1 carcinogen by the International Agency for Research on Cancer (IARC) (e.g., see [64]).…”
Section: Polymer Nanofibresmentioning
confidence: 99%